Effect of IL-36γ expression on chronic periodontitis with an increase in NF-KB signaling pathway - Amir Reza Babaloo; Adileh Shirmohammadi; Shima Ghasemi; Siamak Sandoghchian; Sahel Parvan; Nazanin Fathi (Tabriz University of Medical Sciences, 2019)
Background. An inappropriate inflammatory response is the cause of many common diseases, especially periodontitis. Considering that no studies have been carried out to investigate the effect of IL-36γ on chronic periodontitis, this study aimed to investigate the inflammatory mechanism of IL-36γ by stimulating macrophage cells using NF-KB pathway. Methods. This experimental study was performed on 50 healthy individuals and 50 subjects with chronic periodontitis. In this study, macrophage cells were extracted first, and then RNA was isolated from all the samples using TRIzol method. Subsequently, the rate of IL-36γ gene expression was analyzed and compared using real-time PCR technique. Additionally, immunofluorescence (IF) technique was used to investigate the rate of inflammation. The rate of NF-Kb expression was also measured via western blot technique. Finally, statistical analysis of the samples was carried out using appropriate statistical methods with SPSS 17. Results. The results showed that the rate of IL-36γ expression in subjects with periodontitis was higher compared to healthy subjects (P<0.05). Moreover, the results showed that following treatment of cells with TLR4, the rate of IL36γ expression increased significantly, especially during the 12-hour period after treatment. Conclusion. This indicates that after stimulating the TLR pathways, the rate of IL-36γ expression will probably increase.